2018
DOI: 10.1021/acs.iecr.7b04993
|View full text |Cite
|
Sign up to set email alerts
|

Removal of SO2 with Sodium Sulfite Solution in a Rotating Packed Bed

Abstract: High efficiency and compact design of the desulfurization technology is necessary to meet the strict emission requirement of the marine environment. A rotating packed bed (RPB), having high mass transfer efficiency and small size, is an excellent choice for SO2 removal from the exhaust gas in ships. In this work, SO2 removal in a laboratory and a pilot RPB with sodium sulfite solution were investigated. Experimental results show that the SO2 concentration at the gas outlet of the RPB can decrease sharply and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…A NO x removal efficiency of 67.4% had been obtained. e results demonstrated that high liquid-gas ratio could enhance the mass transfer at the liquid-gas interface in the RPB reactor [6]. erefore, it promoted the NO oxidation obviously and the NO x absorption slightly during the cyclic scrubbing process in the RPB reactor.…”
Section: Effect Of Coexisting Somentioning
confidence: 89%
See 2 more Smart Citations
“…A NO x removal efficiency of 67.4% had been obtained. e results demonstrated that high liquid-gas ratio could enhance the mass transfer at the liquid-gas interface in the RPB reactor [6]. erefore, it promoted the NO oxidation obviously and the NO x absorption slightly during the cyclic scrubbing process in the RPB reactor.…”
Section: Effect Of Coexisting Somentioning
confidence: 89%
“…At present, a number of De-SO x and De-NO x technologies have been developed for large vessels [3]. Some wet flue gas desulphurization (WFGD) techniques have been successfully applied on board to remove SO x effectively [6]. ough selective catalytic reduction (SCR) and exhaust gas recirculation (EGR) are two relatively mature De-NO x methods for marine diesel engines [7] and their NO x challenges efficiencies are high enough, there are still some problems limiting their large-scale applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotating packed bed (RPB) reactors, which can generate a centrifugal force up to several hundred times gravity, have been widely applied into homogeneous and multiphase reactions . It has been recognized as a typical process intensification device for both mass transfer and mixing processes .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 As a result, the mass transfer coefficient and micromixing efficiency of a RPB are up to 1-3 orders of magnitude in comparison with a traditional packed bed. [5][6][7] RPBs have been widely used for gas-liquid, liquid-liquid, and gas-liquid-solid systems, such as absorption 8 and distillation, 9 condensation reaction, 2 production of nanoparticles, 10 and catalytic hydrogenation. 11 The mass transfer performance in a RPB can be determined by experimental measurement and mass transfer model.…”
Section: Introductionmentioning
confidence: 99%